Nilai-nilai Dakwah dalam Film Sang Pencerah - Amin, Edi (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2010)
Religious movies have been largely produced nowadays. One of them is Sang Pencerah, a movie directed by Hanung Bramantyo and sponsored by one of the largest religious organization in Indonesia, Muhammadiyah. This is a biography movie from its founder, KH. Ahmad Dahlan. Since it describes about a religious leaders and his central role in establishing Muhammadiyah, we can find many experiences and facts from Dahlan during his proselytizing. Muhammadiyah is known as a proselytizing organization, with the main principles of amar makruf nahi munkar (call for goodness and forbidden disavowal). This article presents the proselytizing dimensions by Dahlan as seen in the movie.